PARAPHARYNGODON SANJUANENSIS (NEMATODA: PHARYNGODONIDAE) PARASITIZING PHYMATURUS CF. PALLUMA (IGUANIA, LIOLAEMIDAE) IN SAN JUAN PROVINCE, ARGENTINA - Castillo, Gabriel Natalio (2022)
Within the oxiuros, the genus Parapharyngodon is characterized by parasitizing mainly reptiles. In Argentina, up to now four species of Parapharyngodon spp. have been mentioned; Parapharyngodon sanjuanensis Ramallo, Bursey, Castillo & Acosta, 2016, Parapharyngodon riojensis Ramallo, Bursey & Goldberg, 2002, Parapharyngodon bainae Pereira, Sousa & Lima, 2011 and Parapharyngodon sceleratus Freitas, 1957. We mention the first record of the nematode P. sanjuanensis in the lizard Phymaturus cf. Palluma Molina, 1782 in the locality of Laguna Blanca, San Juan province, Argentina. Two male specimens of P. cf. palluma were analyzed. 65 nematodes P. sanjuanensis (2 males and 63 females) were recorded, with mean intensity of 32.5 and prevalence of 100%. Morphometric data for males and females are provided. The genus Phymaturus are the reptiles with the highest parasitic intensities of reptiles in Argentina. This is probably associated with its herbivorous diet and limited range of action. We mention a new parasite-host interaction, expanding the geographic distribution of the parasite.